Исследования вентильного двигателя с внутренними постоянными магнитами при двух способах соединения фаз обмотки статора - Радимов, Игорь Николаевич; Рымша, Виталий Викторович; Гулый, Михаил Викторович; Кравченко, Петр Алексеевич (НТУ "ХПИ", 2010)
Приведены результаты расчетных и экспериментальных исследований вентильного двигателя с внутренними постоянными магнитами. Проанализировано создание электромагнитного момента и ЭДС при схемах соединения фаз обмотки статора "звезда" и "треугольник"

Results of calculation and experimental investigations of a brushless DC motor with interior permanent magnets are described. Generation of electromagnetic torque and EMF in “star” and “triangle” wiring schemes of the stator phase winding is analyzed
Investigation of a brushless dc motor with interior permanent magnets at two modes of the stator phase winding connection
Keywords: электромеханика; преобразователи энергии; магнитопровод; ротор; brushless DC motor; interior permanent magnets; exterior permanent magnets; finite element method; electromagnetic torque; electromotive force